Fame [videorecording (DVD)] - Parker, Alan, 1944-2020-; Cara, Irene, 1959-; Curreri, Lee; Dean, Laura, 1963-; Franceschi, Antonia; Allen, Debbie, 1950-; Ray, Gene Anthony (Warner Home Video, 2009)
Story about students at the High School of Performing Arts, New York. Dance sequences include an audition, classes, a ballet solo by Antonia Franceschi, and the ensemble numbers "Fame" and "I sing the body electric."